Broader Visual Orientation Tuning in Patients with Schizophrenia - Rokem, Ariel; Yoon, Jong H.; Ooms, Renata E.; Maddock, Richard J.; Minzenberg, Michael; Silver, Michael A. (Frontiers in Human Neuroscience, 2011)
Reduced gamma-aminobutyric acid (GABA) levels in cerebral cortex are thought to contribute to information processing deficits in patients with schizophrenia (SZ), and we have previously reported lower in vivo GABA levels in the visual cortex of patients with SZ. GABA-mediated inhibition plays a role in sharpening orientation tuning of visual cortical neurons. Therefore, we predicted that tuning for visual stimulus orientation would be wider in SZ. We measured orientation tuning with a psychophysical procedure in which subjects performed a target detection task of a low-contrast oriented grating, following adaptation to a high-contrast grating. Contrast detection thresholds were determined for a range of adapter-target orientation offsets. For both SZ and healthy controls, contrast thresholds decreased as orientation offset increased, suggesting that this tuning curve reflects the selectivity of visual cortical neurons for stimulus orientation. After accounting for generalized deficits in task performance in SZ, there was no difference between patients and controls for detection of target stimuli having either the same orientation as the adapter or orientations far from the adapter. However, patients’ thresholds were significantly higher for intermediate adapter-target offsets. In addition, the mean width parameter of a Gaussian fit to the psychophysical orientation tuning curves was significantly larger for the patient group. We also present preliminary data relating visual cortical GABA levels, as measured with magnetic resonance spectroscopy, and orientation tuning width. These results suggest that our finding of broader orientation tuning in SZ may be due to diminished visual cortical GABA levels.